In our own words: Pacific Early Career Academics (PECA) and Pacific knowledges in higher education pedagogical praxis. Issue 1 (2nd January 2021) - Thomsen, Patrick; Leenen-Young, Marcia; Naepi, Sereana; Müller, Karamia; Manuela, Sam; Sisifa, Sisikula; Baice, Tim
ABSTRACT: Limited attention has been paid to the experiences of Pacific Early Career Academics (PECA) in utilising their culture-specific systems of knowledge in their pedagogical practice. As a cross-section of PECA employed in a variety of disciplines and faculties, we explore how our Pacific identities infuse our pedagogical approaches in a way that forefronts the significance and validity of Pacific knowledges. We argue that, despite academia perpetually undervaluing Pacific knowledges and even without formal Pacific pedagogical training, PECA prioritise Pacific knowledges in the way we think, teach, and communicate in the classroom. Further, PECA contribute to a reshaping and remodelling of curriculum and delivery that is culturally responsive and enhances learning and teaching spaces significantly. Thus, we believe that universities need to commit to not only hiring more Pacific academics, but also provide greater institutional and financial support for the development of PECA networks across different faculties, schools and disciplines. We also argue that to help retain PECA, Pacific pedagogical praxis must be understood as part of wider pastoral care efforts.